Development of a CD19-TAC therapy in preparation of human trials - Helsen, C.W.; Hayes, D.; Hammill, J.; Aarts, C.; Bader, A.G.; Bramson, J. (Cytotherapy (Oxford, England), 2019)
The T cell antigen coupler (TAC) is a novel chimeric receptor designed to redirect T cells in an MHC-independent fashion and to activate T cells by co-opting the natural TCR receptor. In vitro and in vivo assessments of TAC T cells in solid tumor models (Helsen et. al. Nature Communications) have revealed that TACs mediate biological effects that are distinct from conventional chimeric antigen receptors (CARs), providing safety advantages, including greater target selectivity and reduced off-target toxicity. Here, we present the preclinical data of a CD19 targeted TAC T cell product in preparation of Phase I clinical trials. CD19-specific anti-cancer activity was established in vitro and in vivo using multiple liquid tumor models such as NALM6 (acute lymphoblastic leukemia), Jeko-1 (Mantle Cell Lymphoma) and Raji (Burkitt's lymphoma). In all cases, administration of TAC engineered T cells led to tumor regression and long-term tumor control. Mice that responded to treatment were resistant to tumor regrowth in tumor re-challenge experiments. This resistance was specific to CD19-positive tumors and absent in CD19-negative control tumor cells, suggesting the development of TAC T cell persistence. Mice treated with two dose levels were subject to detailed health monitoring and included an assessment of serum cytokines, T cell expansion, clinical chemistries and organ histopathology. These data confirm our previous results produced by other TAC constructs and provide further evidence highlighting its potential as an effective and well tolerated T cell therapy that may be accessible to a broad patient population. A CD19 TAC therapy is expected to enter clinic testing in H1 2019 in patients with DLBCL.